Supera Stent Implantation with Ultrasound Guidance for Complex Ostial Lesions of Superficial Femoral Artery by Retrograde Approach: The SUGAR Technique - Virender Singh Sheorain; Rajiv Parakh; Tarun Grover; Tapish Sahu; Ashutosh Aher (Journal of Clinical Interventional Radiology ISVIR)
Purpose The aim of this study was to describe a modified technique for accurate deployment of the Supera stent under ultrasound (US) guidance for complex lesions involving superficial femoral artery (SFA) ostium without jailing profunda femoral artery (PFA) by retrograde approach. Technique Retrograde pedal access was initially taken in all the cases. The stenotic or occlusive femoropopliteal lesions involving the SFA ostium were crossed retrogradely and additional contralateral common femoral artery (CFA) access was taken only if we failed to cross the lesion. In addition to fluoroscopy, extravascular US guidance was freely used whenever required throughout the procedure. After desired predilatation of the SFA lesion, US guidance (gray scale and color Doppler) was used to start deployment of the proximal few centimeters of Supera stent ensuring that the landing of first crown was exactly from the SFA ostium not extending into CFA or jailing the PFA ostium. The rest of the stent was deployed under fluoroscopic guidance. Retrograde pedal access site hemostasis was achieved by manual compression. The Supera stent implantation with Ultrasound Guidance for complex ostial lesions of superficial femoral Artery by Retrograde approach (SUGAR) technique was applied successfully in 35 patients (mean age 58.1 ± 4.4 years; 24 males) with critical limb ischemia via the distal pedal approach. No access site or remote complications were observed. Conclusion The SUGAR technique has superior advantage of utilizing a simple tool like extravascular US in addition to fluoroscopy for retrograde Supera stent deployment by allowing very precise landing at SFA ostium, bypassing the need for multiple oblique projections, unwanted radiation exposure, and extra contrast dye overload.